The Effect of Relative Performance Evaluations on Employee Judgments of and Behavioral Responses to Managerial Monitoring - Burke, Joseph; Samet, Jordan A. (The Accounting Review, 2026)
ABSTRACT We examine whether and how a widely established finding—employees respond negatively to managerial monitoring—generalizes to different performance-evaluation systems. We predict that relative performance evaluations (RPEs), a common evaluation feature in multiagent settings, attenuate employees’ negative responses to managerial monitoring. The results of our experiment support our theory. Consistent with prior literature, we find that without RPE, employees respond significantly more negatively to managerial monitoring compared to no monitoring. However, we find that the effect of managerial monitoring on employee responses is moderated in the presence of RPE—employees respond similarly regardless of whether their manager implements a monitoring control. We provide robust analyses to support our theory-derived mechanisms, demonstrating that our results are driven by employees’ fairness perceptions of managers’ monitoring decisions. Collectively, this study aids in the understanding of how and under what circumstances managerial monitoring may be more or less beneficial. Data Availability: Available upon request. JEL Classifications: C90; D91; J31; M40.